Porositas Produk Olahan Jahe Merah terhadap Variasi Suhu Evaporasi-Kristalisasi dan Persentase Gula Batu - Kurniyanto, Valentinus Enrico; Sari*, Dessy Agustina (Jurnal Teknologi, Fakultas Teknik, Universitas AKPRIND Indonesia, 2023)
Red ginger (Zingiber officinale var. Rubrum) is one of the most popular plants in Indonesia. Generally, the processed product is distributed in the community in the form of red ginger extract powder. This study examines the production of processed red ginger products in the form of red ginger powder with variations in temperature treatment (80 and 90°C) and the percentage of sugar cubes (60 and 100%). The purpose of this study was to determine the effect of temperature variations and crystallization agent levels on the porosity value of red ginger powder products, both research results and commercial products that have been circulating in the market. Analysis of test results obtained from scanning electron microscope (SEM) surface morphology images with prior conversion to matrix data The analysis step utilized the Origin program version 2019b. The results of the study with four treatments gave a positive value for porosity. The best treatment obtained was at 90°C and 100% sugar content for residual red ginger raw material (pulp). The highest porosity value for red ginger powder was 76.48%. Meanwhile, the highest commercial product was 77.00%. Indirectly, the research product has a porosity value that is close to the commercial product. The surface area of the product can significantly influence the porosity value between powder and granule products from ginger processing in an effort to increase post-harvest shelf life.